Social environment, low-carbon cognition and low-carbon consumption behaviors of youth groups: evidence from Xizang, China - Ma, Huifang; Chen, Qin (Frontiers in Psychology, 2025)
IntroductionGlobal warming has profoundly transformed the natural environment and significantly impacted people’s production methods, thereby promoting low-carbon consumption behaviors. While numerous scholars have examined the factors influencing low-carbon consumption behavior, their analyses predominantly rely on classical theoretical frameworks such as planned behavior theory, value-belief-norm theory and The ABC attitude theory. However, there is a notable scarcity of studies investigating the relationship between the social environment and low-carbon behaviors among youth groups. To address this gap in the literature, we aim to explore how the social environment influences youth groups’ low-carbon consumption behaviors, as well as identify the mechanisms through which this influence may manifest.MethodsThis study examines the factors influencing low-carbon consumption behavior from three perspectives: the social environment, low-carbon cognition, and conformity consumption. A theoretical model of low-carbon consumption has been developed, and data were collected through a questionnaire survey involving 600 young individuals in the Xizang Autonomous Region. The hypothesized relationships were tested using structural equation modeling techniques.ResultsThe findings indicate that the social environment has a significant positive impact on both low-carbon cognition and behavior. Furthermore, low-carbon cognition is shown to positively influence low-carbon behavior. In terms of the relationship between the social environment and low-carbon behavior, it is found that low-carbon cognition acts as a mediating variable. Additionally, it was observed that lower levels of conformity consumption negatively moderate both the relationship between the social environment and low-carbon behavior as well as that between low-carbon cognition and behavior.DiscussionThese findings suggest that engaging young individuals not only fosters environmental awareness but also promotes sustainable consumption, thereby establishing a solid foundation for the protection and enhancement ofour ecological environment. Furthermore, it is essential to disseminate the concept of low-carbon consumerism through various media channels and methodologies. This approach aims to enhance young individuals’ understanding of low-carbon principles, guiding them toward more scientifically informed consumption habits while reducing tendencies for blind conformity.